The Study of Neuropsychological Functions in Myopes, Following an Intervention of Trataka Yoga Kriya (International Journal of Physiology, 2020)
Aim of Study: To evaluate the effects of Trataka yoga on neuropsychological functions in myopic subjects.Methodology: Out of 36 myopes recruited for the study, 25 subjects were considered for statistical analysis.Digit Span Test and Complex Figure test were measured before and after an intervention of Trataka yogakriya for 3 weeks.Results: In the present study, post Trataka yoga kriya intervention, Complex figure test results showed anincrease in mean scores from 31.32 to 34.20 and Digit span test results showed an increase in mean scoresfrom 7.32 to 7.96, which was found to be statistically significant.Conclusion: Our study concluded that Trataka yoga has a significant effect on neuropsychological functionsin myopes Further regular Trataka yoga kriya practice can be used as an inexpensive, simple and nonpharmacological means as a protective factor against cognitive deterioration.